Using Shared Services to Mitigate Boomtown Impacts in the Bakken Shale Play: Resourcefulness or Over-adaptation? - Smith, Kristin K; Haggerty, Julia H; Kay, David L; Coupal, Roger (Journal of rural and community development, 2019)
Unconventional oil and gas development frequently creates challenges for local government service provision and production. This case study unites research on shared services and energy impacts through a qualitative analysis of a suite of shared services experiments pursued in the context of the boom in unconventional oil and gas development in northwestern North Dakota, United States. The article examines how the unique circumstances of energy boomtown dynamics in remote and rural areas shape the feasibility and form of shared services as solutions to acute service provision crises. The findings demonstrate that communities can deploy substantial innovation in response to the shocks of an energy boom, complicating assumptions about social disruption and community passiveness. However, the use of shared services also reinforced unrealistic projections about the duration and long-term benefits of the boom. In some instances, the use of shared services enabled extravagant projects with questionable future sustainability.